Gender Differences in the Clinical Presentation of Cluster Headache: A Role for Sexual Hormones? - Allena, Marta; De Icco, Roberto; Sances, Grazia; Ahmad, Lara; Putortì, Alessia; Pucci, Ennio; Greco, Rosaria; Tassorelli, Cristina (Frontiers in Neurology, 2019)
Introduction: Cluster Headache (CH) is a well-characterized primary headache that mostly affects men, although a progressive decrease in the male-to-female ratio has occurred over time. Available, but partly discordant, data on gender-related differences in CH suggest a more marked overlapping with migraine features in female subjects. The aim of this study is to carefully evaluate the female/male distribution of the typical migraine-associated symptoms and of other features of the disease in a large and well-characterized clinical population of CH subjects. Materials and Methods: We enrolled consecutive CH patients regularly followed at the tertiary Headache Science Center of the IRCCS Mondino Foundation of Pavia (Italy) who attended the Center for a CH bout between September 2016 and October 2018. The subjects were requested to fill in a semi-structured questionnaire focused on the presence of migraine-associated symptoms, familiarity for migraine and, for women, the relationship of CH onset with the reproductive events of their life. These data were compared and integrated with those recorded over time in our clinical database, including demographics and clinical characteristics. The primary outcome was the gender distribution of subjects who satisfied ICHD-III criterion D for migraine-associated symptoms. The secondary outcomes were represented by the gender distribution of individual migraine-associated symptoms and of other disease features included in the questionnaire and/or in the clinical database. Results: Data from 163 males (mean age 41.46 ± 10.37) and 87 females suffering of CH (mean age 42.24 ± 11.95) were analyzed. We did not find a different distribution between sexes as regards the primary outcome measure (F 73.6%, M 65.6%, p = 0.200). However, when we analyzed the occurrence of individual symptoms, nausea and osmophobia were reported more frequently by women (p = 0.048, p = 0.037, respectively). Ptosis and nasal congestion were predominant in females (p = 0.017 and p = 0.01, respectively), while enlarged temporal artery was more frequently reported by men (p = 0.001). Distribution of pain across the head tended to be larger in women, extending more frequently to the zygomatic (p = 0.050), parietal (p = 0.049), and frontal (p = 0.037) regions. Women had a longer mean attack duration (p = 0.004) than men. In CH women the onset of disease often corresponded with moments of important changes in the levels of sexual hormones (menarche, post-partum, menopause). Concomitant thyroid diseases and psychiatric disorders were observed more frequently in women than in men, while snoring and smoking habit was reported by a higher percentage of men than women. Conclusion: We confirmed the presence of distinct gender-related differences in CH and added some novel information that lends credibility to the hypothesis of a closer phenotypical similarity between CH and migraine in the female sex. These observations are relevant for advancing our knowledge on CH pathophysiology, as well as for a more refined diagnostic framing and improved management of the disease.